PERAN PROFITABILITAS DALAM MEMEDIASI PENGARUH PERTUMBUHAN PERUSAHAAN DAN STRUKTUR MODAL TERHADAP CORPORATE SOCIAL RESPONSIBILITY - Pradnyani, I Gusti Agung Arista; Purbawangsa, Ida Bagus Anom; Artini, Luh Gede Sri (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.06.NO.05.TAHUN 2017, 2017)
The aim of this study is determine how profitability mediating the effects of the company's growth and capital structure to Corporate Social Responsibility. The population in this study are manufacturing companies listed in Indonesia Stock Exchange. Sample was conducted by purposive sampling method and then the number of samples is 37 companies. The research data is secondary data obtained from the website of the Indonesia Stock Exchange and the Indonesian Capital Market Directory from 2013 until 2015. Data analysis by path analysis technique with SPSS 23 software. The results of this study showed that: (1) the company's growth and capital structure had positive and significant impact on CSR. (2) the company's growth and capital structure had positive and significant impact on profitability. (3) profitability had positive and significant impact on CSR. (4) profitability is able to mediate the effect of company's growth and capital structure on Corporate Social Responsibility significantly .
Keywords: company' s growth, capital structure, profitability, and Corporate Social Responsibility